A Review of Condensation Frosting. Issue 2 (3rd April 2017) - Nath, Saurabh; Ahmadi, S. Farzad; Boreyko, Jonathan B.
Abstract: The accretion of ice and frost on various infrastructure is ubiquitous in cold and humid environments, causing economic losses amounting to billions of dollars every year worldwide. The past couple of decades have seen unprecedented advances in the fields of surface chemistry and micro/nanofabrication, enabling the development of hydrophobic and superhydrophobic surfaces that promote facile deicing and/or passive anti-icing. However, in the light of new discoveries regarding the incipient stages of frost formation, it is becoming increasingly clear that the problems of icing and frosting are not one and the same. Thus, passive anti-icing strategies do not exhibit anti-frosting behavior, and the development of passive anti-frosting surfaces remains an unsolved problem. In this review, we provide a critical discussion of condensation frosting and show how the emerging new phenomena of frost halos, interdroplet ice bridges, and dry zones that comprise the incipient stages of frosting set it apart from the conventional problem of icing. Subsequently, we discuss possible strategies to break the sequential chain of events leading to pervasive frost growth.